Community Participation in Supporting the Development of Nino Konis Santana National Park As a Tourism Destination in Timor Leste - do Ceu Fatima, Arlindo; Jesus Ximenes , Maria de; Bruno das Neves, Cipriano (Greenation Research & Yayasan Global Resarch National, 2023)
Community Participation in Supporting the Development of Nino Konis Santana National Park as a Tourism Destination in Timor Leste. The purpose of this study is to analyze the extent of the role of government and society in supporting efforts to develop the Nino Konis Santan National Park in Timor Leste. The main things that can be seen are the role of government, community participation, and government and community efforts in supporting the development of the national park.This study uses a qualitative method with a case study method approach. The samples taken in this study were the Tutuila Sub-district Head, two village heads and one from the forestry police staff and three local communities selected by purposive sampling. The results of this study include: (1) The level of public understanding about nature protection is still very low (2) The level of socialization of conservation policies is still not optimal (3) There is no world of work for the community (4) There is no provision of full authority to local officials, so that it influences decision making in implementing policies (still centralized (5) There is no public awareness about the importance of national parks in Timor Leste.